ANALISIS KINERJA PROYEK PEMBANGUNAN RUMAH SAKIT PANTI BHAKTININGSIH CHARITAS KECAMATAN BELITANG, KABUPATEN OKU TIMUR - Augustina Legislatifa, Poppy; Firda, Ani; Hendric, Adefan; Sadik Islami, Fajar; Fuad, Indra Syahrul (LATERAL: Jurnal Teknik Sipil, 2024)
In a project, planning and controlling time and cost is parts of contruction management project completely, Earned Value concept is one of method that can monitoring project’s performance from the cost and time goodly. This research has aim to know project’s performance from the time and cost side weekly, predict cost and time for job finishing rest of jobs. So it can get correction action what next will do for project developing. It use Earned Value Analisys by collecting data in the field development project Panti Bhaktiningsih Charitas Belitang Hospital. The results of the analysis of the Panti Bhaktiningsih Charitas Belitang Hospital construction project, namely the actual cost to complete the Panti Bhaktiningsih Charitas Belitang Hospital construction project from May 2017 to July 2018 was Rp. 19,883,148,800 with a Schedule Performance Index (SPI) value of 0.887 while the Cost Performance Index (CPI) was 1.034, which means that the project experienced delays in terms of schedule but incurred actual costs that were less than the work that had been carried out. Estimate to Completion (ETC) value is Rp. 7.333.436.666 and Estimate Cost at Completion (EAC) value is Rp.27.216.585.466,00 whereas Estimated Completion Date (ECD) value become 558 days from finishing the project.